Industrial concrete floors: Evaluation of electrostatic dissipative properties according to IEC 61340-4-1. (25th April 2022) - Heinlein, Ulli; Freimann, Thomas
Highlights: Concrete was tested for its electrostatic dissipative properties. Samples were measured on their resistance at varying relative humidities. Fresh concrete compositions were varied. In-situ tests on unmodified concrete slabs verified the laboratory results. Unmodified concretes showed sufficiently low electrical resistances down to 30 % RH. Abstract: Work areas for electronic components or explosive substances must have dissipative floors to prevent electrostatic discharges. Up to now, this is ensured via organic floor coatings with a defined electrical resistance. Electrically conductive concrete mixtures have also been proposed for dissipative floors. However, no investigations were done under practice-oriented conditions and the applicable IEC 61340 for electronic manufacturing areas. The following article tested various concrete mixtures for their electrical resistances and evaluated them according to the limit values of IEC 61340. The environmental conditions strongly determined the dissipation capacity. Unmodified concrete mixtures showed electrical resistances in the limits of dissipative floors between 30 and 100  % relative air humidity. Thus, when air humidification is available, unmodified concrete can be used as dissipative floor. The addition of conductive fibers lowered the electrical resistance significantly but led quickly to resistances below minimum values for personal protection. In order to verify the laboratory measurements, existing industrial concrete floors were measured. Slabs with 30 years of age showed similar electrical resistances as laboratory specimens. Measurements using a 4-point Wenner probe array showed comparability to literature values.